Effectiveness Test of Angsana Leaf (Pterocarpus Indicus) as Antibacterial Shigella dysenteriae - Ester Fani Indriani; Aulia Nova Rahmadita; Rakhmad Dhiya Ulhaq; Ridan Rizkiani; Nazwa Vidya Malik; Risnawati Risnawati (Jurnal Media Analis Kesehatan, 2023)
Diarrhea is an endemic disease and the main cause of death in the post-neonatal period. The disease caused by the diarrhea-causing bacteria Trichophyton rubrum continues to be a problem throughout the world, especially in Indonesia. The aim of this research was to determine the effect of the bioactive compound content in Angsana (Pterocarpus indicus) leaf extract on Shigella dysentriae, the diarrhea disease vector. The research design used in this study was a post test only control group design. The results of the study showed that extraction using 96% ethanol solvent had an effect on Shigella dysentriae bacteria. Angsana leaf extract with 96% ethanol solvent has an effect at a concentration of 30% on Shigella dysentriae bacteria. Testing of the bioactive compound content in Angsana leaf extract using 96% ethanol solvent was analyzed using GC-MS to determine the bioactive compound profile of Angsana leaves. The largest composition component with a percentage content of 22.49%. The three components of this compound are: Lup–20 (29)–en–3-one; 13,27–Cycloursan–3-one; dan 4,6a,6b,8a,11,11,14b–Octamethyl-1,4,4a,5,6,6a,6b,7,8,8a,9,10,11,12,12a,14,14a, 14b–octadecahydro-2H–picen–3–one